2018
DOI: 10.3390/nu10070921
|View full text |Cite
|
Sign up to set email alerts
|

l-Citrulline Supplementation: Impact on Cardiometabolic Health

Abstract: Diminished bioavailability of nitric oxide (NO), the gaseous signaling molecule involved in the regulation of numerous vital biological functions, contributes to the development and progression of multiple age- and lifestyle-related diseases. While l-arginine is the precursor for the synthesis of NO by endothelial-nitric oxide synthase (eNOS), oral l-arginine supplementation is largely ineffective at increasing NO synthesis and/or bioavailability for a variety of reasons. l-citrulline, found in high concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(171 citation statements)
references
References 173 publications
(253 reference statements)
6
143
0
2
Order By: Relevance
“…However, oral Arg supplementation is largely ineffective due to gastrointestinal and hepatic extraction of Arg. Alternatively, oral Citrulline supplementation consistently increases the bioavailability of Arg and NO in plasma and tissue [24]. Most of the orally administered Citrulline is removed from circulation by the kidneys, and it is efficiently converted into Arg [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, oral Arg supplementation is largely ineffective due to gastrointestinal and hepatic extraction of Arg. Alternatively, oral Citrulline supplementation consistently increases the bioavailability of Arg and NO in plasma and tissue [24]. Most of the orally administered Citrulline is removed from circulation by the kidneys, and it is efficiently converted into Arg [25].…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is a gas-signal molecule with various physiological functions, including regulating the balance of blood ow and oxygen demand and neurovascular coupling in the brain [22][23]. Endogenous NO was mainly generated from the citrulline-arginine-NO pathway [24]. Previous studies have shown that L-citrulline supplementation increased the bioavailability of L-arginine and promoted NO synthesis [24].…”
Section: Discussionmentioning
confidence: 99%
“…L-citrulline is non-essential amino acid that found in abundance in watermelon. Potential beneficial effects on cardio-metabolic health [119,120] have been reported. In a recent study, 22 patients with flow mediated dilation of the brachial artery (< 5.5%) were recruited take 800 mg/day of L-citrulline for 8 weeks.…”
Section: L-citrullinementioning
confidence: 99%